A novel protein-engineered dsDNA-binding protein (HU-Simulacrum) inspired by HU, a nucleoid-associated DNABII protein - Thakur, Bhishem; Gupta, Archit; Guptasarma, Purnananda (Elsevier, 2021)
HU, a DNA-binding protein, has a helical N-terminal region (NTR) of ∼44 residues and a beta strand- and IDR-rich C-terminal region (CTR) of ∼46 residues. CTR binds to DNA through (i) a clasp (two arginine/lysine-rich, IDR-rich beta hairpins that bind to phosphate groups in the minor groove), (ii) a flat surface (comprising four antiparallel beta strands that abut the major groove), and (iii) a charge cluster (two lysine residues upon a short C-terminal helix). HU forms a dimer displaying extensive inter-subunit CTR-CTR contacts. A single-chain simulacrum of these contacts (HU-Simul) incorporating all DNA-binding elements was created by fusing together the CTRs of Escherichia coli HU-A and Thermus thermophilus HU. HU-Simul is monomeric, binds to dsDNA and cruciform DNA, but not to ssDNA.
Only IISER Mohali authors are available in the record.
Keywords: protein-engineered; dsDNA-binding; protein (HU-Simulacrum); HU